The state and prospects of TB control service in Russia during the COVID-19 pandemic - O. B. Nechaeva (Туберкулез и болезни лёгких)
The objective: to determine the state and prospects of TB control services including the period during the COVID-19 pandemic.Materials. Data from Federal Statistic Surveillance Forms no. 4, 8, 14, 14-DS, 30, 33, 47, and 61 were analyzed. The number of those died is presented as per the data of Rosstat.Research methods: epidemiological and statistical analysis, expert assessment, and content analysis of publications and regulations.Results. In Russia in the second decade of the XXI century, there was a significant improvement of tuberculosis situation. From 2010 to 2019, the reduction of the rates was the following: incidence – from 77.2 to 41.2 per 100,000 population (by 46.6%); prevalence – from 177.5 to 86.4 per 100,000 population (by 51.3%); mortality – from 15.4 to 5.1 per 100,000 population (3-fold reduction).In recent years, one can anticipate the stabilization of HIV situation. Over 10 years (2006-2015), the average growth rate of indicators was the following: incidence – by 9.8%, prevalence at the end of the year – by 9.4%, mortality – by 26.6%. In 2016-2019, HIV incidence became stable (2019 – 54.6 per 100,000 population). In 2019, for the first time HIV mortality decreased by 2.1% and reached 13.7 per 100,000 population. The number of lethal TB/HIV co-infection cases is going down. People at the age of 15-34 fall ill (2019 – 37.6%) and die (23.6%) less often versus all new cases and those who died of HIV infection. Russia has the highest coverage of the population with HIV tests (28.5%).Epidemics of tuberculosis and coronavirus infection are developing in the opposite directions. High rates of COVID-19 are observed in regions with low tuberculosis rates, therefore the COVID-19 pandemic will not result in the increase of tuberculosis incidence in the population that is predominantly not infected with tuberculosis. Conversely, in regions with a high level of tuberculosis infection in the population, the number of coronavirus cases is significantly lower.In Russia, in the near future COVID-19 will not contribute to the increase in incidence and mortality of tuberculosis and HIV infection. The negative effects of the pandemic are partially offset by a sharp reduction in contacts, an increase in lung computed tomography, regular supply of anti-tuberculosis and antiretroviral drugs purchased by the state budgets of different levels, improved patients’ adherence to treatment, and the expansion of hospital-replacing technologies in specialized medical organizations.Facilities, resources and personnel of medical TB control services make it possible to expand their functions to fulfill the goals and objectives of the RF Healthcare Development Strategy for the period up to 2025 for socially significant infectious diseases that pose a biological threat to the population (tuberculosis, HIV infections, and parenteral viral hepatitis).